(untitled) (Journal of the College of Languages (JCL), 2011)
In any language there is some amount of difference between written language (planned) and spoken language (spontaneous). Since planned speech could be considered a form of written language, it could be inferred that there are also differences between planned speech and spontaneous speech. Some of these differences are very clear in terms of syntax, lexis, phonology and discourse. These differences are highlighted in order to make a clear distinction between spontaneous and planned speech. This paper is an attempt to show the differences between the two forms of a language (written & spoken English) as far as number of linguistic features are tackled